2009
DOI: 10.17221/151/2009-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Selection of probiotic bifidobacteria for lambs

Abstract: Twenty-six bifidobacteria were isolated from faecal samples of lambs. The isolates were identified, functional properties (survival ability at low pH and bile conditions) and antimicrobial activities against potential pathogens were determined. From the isolates with suitable properties (13 strains) rifampicinresistant mutants were prepared by gradient plate techniques. This property enabled us to differentiate the administered organism from wild strains because resistance to rifampicin is rare among bifidobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
1
7
1
Order By: Relevance
“…Three days after the application of probiotics, the number of lactobacilli was insignificantly higher in both experimental groups compared to the control, but the differences were not significant (Table 1). This finding is consistent with the results obtained by Vlkova et al (2009), who observed a slight increase in lactobacilli numbers after feeding bifidobacteria to lambs.…”
Section: Discussionsupporting
confidence: 93%
“…Three days after the application of probiotics, the number of lactobacilli was insignificantly higher in both experimental groups compared to the control, but the differences were not significant (Table 1). This finding is consistent with the results obtained by Vlkova et al (2009), who observed a slight increase in lactobacilli numbers after feeding bifidobacteria to lambs.…”
Section: Discussionsupporting
confidence: 93%
“…Properties predicting survival of lactobacilli during passage through the gastrointestinal tract (acid and bile tolerance) were tested as described elsewhere [62]. Briefly, overnight bacterial suspension free of cultivation media was mixed with oxygen-free phosphate buffered saline (OF-PBS) of pH 2 or 3 (pH adjusted with HCl), with OF-PBS buffer (pH 7.2) containing 1%, 2%, or 3% bile extract, or with OF-PBS buffer (pH 7.2) for control.…”
Section: Methods Of Isolation Characterization and Identification Omentioning
confidence: 99%
“…Three published studies support our finding, describing the identification of Bifidobacteria in sheep and the use of this microorganism as a potential probiotic. [42][43][44] In humans, they are generally thought to be a marker of good gut health [41].…”
Section: Discussionmentioning
confidence: 99%